Estado de fragmentación del bosque seco de la cuenca alta del río Cauca, Colombia - Angela María Arcila Cardona; Carlos Valderrama Ardila; Patricia Chacón de Ulloa (Biota Colombiana, 2012)
Using maps of vegetation cover, aerial photographs and field data, we evaluated the fragmentation status of tropical dry forest at the high basin of river Cauca in southwestern Colombia. The study area had 608992 ha, ranging from northern Cauca to central Risaralda. Forest cover represented 1,76% of the analyzed area, scattered in about 1600 fragments with a mean patch area of 6,03 ha. 75% of the forest fragments were separated by a distance of 500 m or more from its nearest neighbour. Only nine fragments had an extension over 100 ha, most of them with dendritic shapes and up to 17 core areas. This configuration would make them behave more like separate small patches than a continuous large patch. In this landscape, edge effect is expected to greatly influence species composition of dry forest fragments. Evaluation of regional species richness should account for the contribution of other arboreal landscape elements. Bamboo forests and riparian forests are especially important since they increase landscape connectivity. In this context, any conservation or restoration initiative should involve management of the landscape matrix, sugar cane and pastures, in order to make them less resistant to the movement or organisms between landscape elements.